Human Body Anatomy and Physiology Module Using Case Method for Biology Students - Aisyah, Siti (Gunung Djati Conference Series, 2025)
The purpose of this study was to describe the structure of the developed case-based human anatomy and physiology module. To determine the responses of the lecturers in charge of the course to the case-based human anatomy and physiology module. To determine the students' responses to the case-based human anatomy and physiology module. The development research method is a type of research that produces a product rather than testing a theory. The results of this study: the developed case-based human anatomy and physiology module has been declared feasible (4.35) based on the assessment of material experts, reviewed from the content and presentation aspects of the material. The lecturers in charge of the course gave a positive response to the case-based human anatomy and physiology module (4.36), reviewed from the indicators of ease and effectiveness/benefit. Students of the biology study program, FMIPA UNIMED, class of 2021, gave a positive response to the case-based human anatomy and physiology module (4.13), reviewed from the indicators of interest, ease and effectiveness/benefit.